Global Business, 4th Edition - Mike W. Peng (Cengage Learning, 2020)
Introduce your students to success in global business today with a strategic approach to international business topics and unique coverage not found in other texts. GLOBAL BUSINESS, 4th Edition, is the first global business book that asks the big question, "What determines the success and failure of firms around the globe?" Globally renowned scholar and author Mike Peng answers from both an institution-based view and resource-based view in every chapter, bringing an unparalleled continuity to the learning process. The book combines an inviting, conversational style with the latest scholarly research and examples that reflect recent global developments. This edition's comprehensive set of cases from Peng and other respected international experts examines how companies throughout the world have expanded globally. All-new video cases that cover each chapter's opening case and closing case, world maps that connect geography and culture to business decisions, and unique global debate sections that draw students into cutting-edge discussions help you teach students to think independently and view business challenges from a truly global perspective.